2016
DOI: 10.1021/jacs.6b03568
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Olefin Activation Using 3D Aromatic Boron-Rich Cluster Photooxidants

Abstract: Local Identifier(s): UCPMS ID: 1604555eScholarship provides open access, scholarly publishing services to the University of California and delivers a dynamic research platform to scholars worldwide. Abstract:We report a discovery that perfunctionalized icosahedral dodecaborate clusters of the type B12(OCH2Ar)12 (Ar = Ph or C6F5) can undergo photo-excitation with visible light, leading to a new class of metal-free photooxidants. Excitation in these species occurs as a result of the charge transfer between low-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 64 publications
2
73
0
6
Order By: Relevance
“…Notably, the initially dark red solution quickly turned colorless. 11 B NMR spectroscopy of this colorless solution revealed a singlet resonance at δ −15 characteristic of a reduced cluster in a [ 2 ] 2- oxidation state 35,36 , which is consistent with the reducing capacity of the thiolate species when exposed to [ 2 ] 0 (Fig. 2d).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Notably, the initially dark red solution quickly turned colorless. 11 B NMR spectroscopy of this colorless solution revealed a singlet resonance at δ −15 characteristic of a reduced cluster in a [ 2 ] 2- oxidation state 35,36 , which is consistent with the reducing capacity of the thiolate species when exposed to [ 2 ] 0 (Fig. 2d).…”
Section: Resultssupporting
confidence: 70%
“…1). Specifically, we demonstrate how dodecaborate clusters 29,3136 featuring a dense layer of rigid pentafluoroaryl functional groups can serve as excellent scaffolds for constructing atomically precise, multivalent organomimetic cluster nanomolecules (OCNs). The perfluoroaryls are able to undergo facile “click”-like nucleophilic aromatic substitution (S N Ar) with a wide range of thiols at room temperature within hours, creating robust carbon–sulfur bonds (80–90 kcal/mol) 37 , thereby producing nanomolecules decorated with well-defined functional surfaces.…”
mentioning
confidence: 99%
“…43 Given our interest in the development of chemistry and applications of perfunctionalized boron clusters, 4446 we reexamined the reactivity of the closo -[B 6 H 7 ] 1− anion. Under microwave heating conditions, the hexaborate anion can be substituted with benzyl bromide electrophiles (Fig.…”
Section: Synthesis Of Perfunctionalized Boron Clustersmentioning
confidence: 99%
“…By utilizing blue LEDs as a light source under controlled conditions, we demonstrated that the perfunctionalized cluster hypercloso -B 12 (OCH 2 Ph) 12 can behave as a powerful photooxidant in the visible light-assisted polymerization of olefins. 46 The proposed mechanism involves the generation of a potent photooxidant by visible light promotion of an electron from a low lying occupied orbital localized largely on the aryl rings and oxygens to the cluster-based LUMO (Fig. 9A).…”
Section: Applications In Catalysis and Materials Chemistrymentioning
confidence: 99%
“…It is well‐known that the boron hydrides (boranes) have attracted a lot of attention because of their potential applications in drug delivery, photoredox catalysts, and materials science, especially for icosahedral [B 12 H 12 ] 2− ( closo ‐dodecaborate) cluster with 12 identical B‐H vertices, that provides the fascinating physicochemical properties serving as building blocks in such diverse areas.…”
Section: Introductionmentioning
confidence: 99%